Enhancement of Vacuum Gas Oil Viscosity Using Ultrasound - Abbas, Fatima Hamid; Naife, Tariq M.; Ahmed, Dalya J.; Hasan, Eman B. (Journal of Petroleum Research and Studies, 2023)
Ultrasonic treatment is a suitable method for refinery processes that Acoustic cavitation is a technique that allows high levels of energy to be released into the liquid, which leads to changes in fluid properties such as a decrease in viscosity. Additionally, it’s an effective way to improve the economic feasibility of physicochemical processing to enhance the quality of the product. In this work, vacuum gas oil with viscosity of 8.4 c.st, provided by Iraqi refineries, was treated by ultrasound radiation and studied the effect of several parameters on viscosity such as sonication time (5,10,15,20,30) min, power amplitude(10,20,30,40,50)watt, and frequency (20,30,40,50) kHr. It was found from the results that the viscosity decreased from (8.4) c.st to (5.82) c.st, which represents a percentage reduction of up to 30.7% compared to the value before treatment. This result was obtained after 30 min., also the 50% of ultrasound power is the appropriate to reduce the viscosity, where The experiment showed that 20 kHz of ultrasound frequency has a decreasing effect on the viscosity as the percentage reaches 30%.